The joy of connecting quantum black dots. (1st January 2023) - Richards, Mark
Abstract : Mark Richards, an atmospheric physicist and senior teaching fellow at Imperial College London, explains why he founded the Blackett Lab Family – the UK's first national network of Black physicists – in 2020.